2017
DOI: 10.1007/978-3-319-57339-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Climbing Down the Hierarchy: Hierarchical Classification for Machine Learning Side-Channel Attacks

Abstract: International audienceMachine learning techniques represent a powerful paradigm in side-channel analysis, but they come with a price. Selecting the appropriate algorithm as well as the parameters can sometimes be a difficult task. Nevertheless, the results obtained usually justify such an effort. However, a large part of those results use simplification of the data relation and in fact do not consider allthe available information. In this paper, we analyze the hierarchical relation between the data and propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…It has been shown that machine learning techniques could perform better than classical profiled side-channel attacks [13]. The researchers first started with simpler machine learning techniques like Random Forest and Support Vector Machines and targets without countermeasures [14], [15], [16], [17], [18]. Already these results suggested machine learning to be very powerful, especially in settings where the training phase was limited, i.e., the attacker had a relatively small number of measurements to profile.…”
Section: A Machine Learning-based Scamentioning
confidence: 99%
“…It has been shown that machine learning techniques could perform better than classical profiled side-channel attacks [13]. The researchers first started with simpler machine learning techniques like Random Forest and Support Vector Machines and targets without countermeasures [14], [15], [16], [17], [18]. Already these results suggested machine learning to be very powerful, especially in settings where the training phase was limited, i.e., the attacker had a relatively small number of measurements to profile.…”
Section: A Machine Learning-based Scamentioning
confidence: 99%
“…Picek et al presented an approach called hierarchical classification [99]. The idea is to explore the natural clustering of the leakage in order to arrange the sensitive variables in a tree structure.…”
Section: Ml-based Side-channel Analysis Of Hardware Vulnerabilitiesmentioning
confidence: 99%
“…For example, if it is known that the power consumption is correlated with the HW of data, then the training labels would be the HW of the intermediate variable. Classical machine learning techniques use a leakage model for classification [35], [36]. Further, these techniques usually require a dimension reduction algorithm, such as principal component analysis (PCA), to select points of interest (POI) of power traces [25].…”
Section: Supervised Learning Attacksmentioning
confidence: 99%